2021
DOI: 10.1021/acs.analchem.1c00385
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Imaging of Cellular Reactive Oxygen Species and Caspase-3 Activity Using a Multifunctional Theranostic Probe for Cancer Diagnosis and Therapy

Abstract: In this work, a multifunctional theranostic nanoprobe (Au–Ag-HM) was skillfully designed for simultaneous imaging of intracellular reactive oxygen species (ROS) and caspase-3 activity. The Au–Ag-HM was fabricated by coloading of silver nanoparticles (AgNPs) and hematoporphyrin monomethyl ether (HMME) to Au nanoflowers (AuNFs). When Au–Ag-HM was devoured by cancer cells, HepG2 cells were used as the model, and under laser irradiation, the photogenerated intracellular ROS by the photosensitizer HMME would induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The WB results showed increased caspase-3 expression in the cells treated with tAgNPs. Relevant studies have shown that AgNPs activate caspase-3 and promote cell apoptosis, thereby inhibiting tumour growth [ 37 , 38 ] . Studies have confirmed that AgNPs increase the caspase-3 level in breast cancer [ 39 ], lung cancer [ 40 ] and other cancers, indicating that tAgNP-treated OC cells complete the apoptosis process through the cysteine protease pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The WB results showed increased caspase-3 expression in the cells treated with tAgNPs. Relevant studies have shown that AgNPs activate caspase-3 and promote cell apoptosis, thereby inhibiting tumour growth [ 37 , 38 ] . Studies have confirmed that AgNPs increase the caspase-3 level in breast cancer [ 39 ], lung cancer [ 40 ] and other cancers, indicating that tAgNP-treated OC cells complete the apoptosis process through the cysteine protease pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct from the design of nanotechnologies for selective sensing of specific species of ROS, these nanomaterials can detect the combined species of ROS by one platform. Several nanomaterials, including PEGylated bilirubin-coated superparamagnetic iron oxide nanoparticles (PEG-BR@SPIONs) ( Lee et al, 2020 ), UCNPs-MoS 2 nanoflakes ( Wang F. et al, 2018 ), multifunctional theranostic nanoprobes (Au−Ag-HM) ( Wang et al, 2021 ), para-aminothiophenol and hemin-decorated gold (Au-PATP-Hemin) nanoprobes ( Cui et al, 2018 ), cyclotriphosphazene-doped graphene quantum dots (C-GQDs) ( Xu et al, 2020 ), ROS-responsive microgel ( Liu et al, 2018 ), and the ionic nanoparticles in a hydrogel microparticle ( Liu et al, 2018 ), are designed under this context. Therein, PEG-BR@SPIONs and Au-PATP-Hemin nanoprobe are promising tools for “turn-on” detection of ROS with demonstrated mechanisms and have potentialities in biological applications.…”
Section: Detection Of Combined Species Of Rosmentioning
confidence: 99%
“…The valuable characteristics of AuNPs, such as their simplicity of synthesis and various surface functionalization mechanisms indicating why gold nanoparticles, are an attractive candidate for further improvement in the clinical diagnosis method, which is thoroughly described in a review article by Gambhir . AuNP-based nanobiosensors are developed as substitutes and facile tools for improving highly sensitive biosensors because of their proper conjugation procedure and superior optical and electrical features. , Also, the LSPR-based technique receives promoting interest because of its wide applications in catalysis, phototherapy, and cellular imaging. In these tools, when AuNPs with particular decorating groups identify their targets, the interaction between both molecules causes a local deviation in the refractive index at the metal surface, which can be screened by spectrometric analysis.…”
Section: Introductionmentioning
confidence: 99%